Evaluation of Gastroesophageal Reflux in Symptomatic Young Infants Using Multichannel Intraluminal pH-Impedance Testing: A large Cohort Study from a Single Center - Sequeira Gomes, Rochelle; Favara, Michael; Abraham, Sheeja; Palma, Joan Di; Aghai, Zubair H. (American Journal of Perinatology, 2024)
Objective This study aimed to assess the use of combined multichannel intraluminal impedance and pH studies (MII–pH) in a large group of symptomatic young infants, to characterize the occurrence of gastroesophageal reflux disease (GERD), and to establish temporal association of the reflux behaviors with gastroesophageal reflux using symptom indices.Study Design This is a retrospective cohort study on 181 infants who underwent MII–pH studies for clinical behaviors that were suggestive of GERD. Symptom index (SI) and symptom association probability (SAP) were used to establish symptom association with reflux. More than 100 GER episodes in 24 hours or acid reflux index > 10% was considered pathological reflux.Results A total of 181 infants (median age: 60 days, interquartile range [IQR]: 34–108) underwent MII–pH studies with median study duration of 22.41 hours (IQR: 21.5–23.32). A total of 4,070 hours of data were analyzed, with 8,480 reflux events (2,996 [35%] acidic, 5,484 [65%] nonacidic). A total of 2,541 symptoms were noted, 894 (35%) were temporally related to reflux events. A total of 113 infants (62.4%) had positive symptom association with SI > 50% and/or SAP > 95% for at least one symptom. There was modest symptom association for choking and gagging, but apnea, bradycardia, and desaturations had poor symptom association. Only 29 infants (16%) had pathological reflux, and only 18 infants (10%) had both pathological reflux and positive symptom association.Conclusion MII–pH can be used to characterize GERD in young infants, along with establishing temporal association with symptoms. Pathological reflux in symptomatic young infants is not common, but symptom association may occur without frequent or acidic reflux.Key Points
Keywords: GERD; MII–pH; symptom association; neonates